2013
DOI: 10.1155/2013/819021
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate Love as a Predictor of Reduced HIV Disease Progression and Transmission Risk

Abstract: Objectives. This study examined if compassionate love (CL) predicts HIV disease progression and transmission risk. Scientific study of CL emerged with Underwood's working model of other-centered CL, defining five criteria: free choice, cognitive understanding, valuing/empowering, openness/receptivity for spirituality, and response of the heart. Method. This 10-year cohort study collected 6-monthly interviews/essays on coping with HIV and trauma of 177 people with HIV in South Florida. Secondary qualitative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
(74 reference statements)
1
13
0
Order By: Relevance
“…In our previous study on CL, we found that high CL towards self had the strongest association with high CL receiving [4]. Participants with high CL towards self were also more likely to give CL to others.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…In our previous study on CL, we found that high CL towards self had the strongest association with high CL receiving [4]. Participants with high CL towards self were also more likely to give CL to others.…”
Section: Introductionmentioning
confidence: 61%
“…In fact, only CL towards self but not other-centered CL, was associated with biological outcome [4]. In an additional study on PLWH [15], we have shown that the spiritual component of CL can also manifest through a view of God/Higher Presence as loving/benevolent.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations